مسح الفطريات الكيراتينية في غبار أرضيات بعض مدارس مدينة العمارة - حسين صالح, طلال (University of Thi-Qar Journal of Science, 2011)
Eighty floor dust samples were collected from some schools in Amarh city to investigate the presence of Keratinophilic fungi using hair- baiting technique . Twenty six species of fungi belonging to twelve genera were isolated and identified The fungi included : six species from the genus chrysosporium ,five species from the genus Microsporum , foure species from the genus Trichophyton , three species from the genus Aspergillus and one species of the following genera : Alternaria, Cladosporium , Drechslera , Fusarium , Mucor , Penicillium , Scopulariopsis and Scytlidium .On the other hand the haemolytic of some species were tested in vitro using blood agar culture ,among them Aspergillus flavus was more efficienty than other .تم جمع ) 41 ( عينة غبار أرضية بعض مدارس مدينة العمارة لمبحث عن تواجد الفطريات الكي ا رتينية فييا وقد استخدمت طريقةالطعم الكي ا رتيني لعزل ىذه الفطريات . تم عزل وتشخيص ) 62 ( نوعاً تعود إلى ) 06 ( جنساً وكان أكثرىا ظيو ا رً جنسChrysosporium )ستة أنواع( ، Microsporum )خمسة أنواع(، Trichophyton )أربعة أنواع (، Aspergillus )ثلاثأنواع(، )ونوع واحد( لكل من الأجناس : Alternaria ، Cladosporium ، Drechslera ، Fusarium ، Mucor، Penicillium ، Scopulariopsis و Scytalidium .اختبرت قدرة بعض الفطريات المعزولة عمى حل الدم عمى الوسط أكار الدم وكان الفطر A . flavus أكثرىا قدرة عمى ذلك .